Pengaruh Metode Belajar Jigsaw Terhadap Keterampilan Hubungan Interpersonal dan Kerjasama Kelompok pada Mahasiswa Fakultas Psikologi - Asmadi Alsa (Faculty of Psychology, Universitas Gadjah Mada, 2010)
This study aims to test the effect of cooperative learning methods, the jigsaw method to interpersonal relationship skill and teamwork of undergraduate students Faculty of Psychology in University A. This study used experimental method with one group and pre posttest design. There are 63 undergraduate students in Educational Psychology Class of 2008/2009 as the subjects. The measurement instrument was Interpersonal Relationship Skill Scale and Teamwork Scale. Interpersonal relationship and teamwork score compared before and after the learning methods were given and tested using paired samples t test. The result shows that comparing the pretest and posttest score of interpersonal relationship variable, we got t ‐1,748 with p = 0,043 (p < 0,05). This is indicated that jigsaw learning method has significant effect to improving the interpersonal relationship skill in undergraduate students. The analysis result in teamwork variable with comparing the pretest and posttest, we got t ‐3,50 with p = 0,001 (p < 0,01) which means the jigsaw learning method significantly effective to improving teamwork skill in undergraduate student